Performance guarantee: Banking guarantee for large and Bonafide Companies - Dharmawan, Johanes Bagus; Murwadji, Tarsisius; Mulyati, Etty (Edelweiss Applied Science and Technology, 2025)
The current conventional guarantee system is fundamentally unfair in that prospective debtors who are large (bonafide) companies, have good intentions in repaying credit, and have a good track record are treated the same as prospective debtors who are small companies with bad intentions in terms of their obligation to provide bank credit guarantees. The provision of bank credit collateral for large companies with good intentions is very detrimental, reducing competitiveness and constituting an unnecessary cost. The Performance Guarantee System was developed from the 5 C Analysis, primarily using both qualitative and quantitative analysis techniques. In the 4 Cs (Capital, Capacity, Character, and Condition of Economy), if the quantitative analysis is feasible, then according to this theory, collateral is no longer necessary. Based on the credit policy established by the OJK, all bank loans must be secured, so this new guarantee is only a performance guarantee because, based on in-depth analysis, it is estimated that the project will run smoothly. According to the Performance Guarantee System Theory, the possibility of loan defaults is small, which means that the possibility of the guarantee being auctioned is also small. Thus, the object of this guarantee can be physically demonstrated and calculated in monetary terms.